2017
DOI: 10.1177/0971333616689203
|View full text |Cite
|
Sign up to set email alerts
|

Disability and Social Exclusion

Abstract: This article explores the experiences of social exclusion of individuals with visual impairment (IWVI) as they negotiate their daily lives in their homes and societal settings in the Oshana and Oshikoto regions of Namibia. Employing qualitative research approach, this research tried to better understand the lived experiences of IWVI. Nine IWVI with ages ranging from 30 to 90 years were initially engaged in focus group discussions, followed by semi-structured in-depth individual interviews. The findings of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
(28 reference statements)
0
11
0
2
Order By: Relevance
“…However, interestingly, those with autism [42] and spina bifida [34] who had high parental support or overprotective parents were even less likely to be employed. Hence, family members, especially parents, played a significant role in finding and maintaining employment [31,43]. The main barriers to employment opportunities for those with autism [44] and intellectual disabilities [26,45] included lack of parental support, time, awareness and knowledge of abilities, parental fatigue and unwillingness to facilitate job search.…”
Section: Support and Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, interestingly, those with autism [42] and spina bifida [34] who had high parental support or overprotective parents were even less likely to be employed. Hence, family members, especially parents, played a significant role in finding and maintaining employment [31,43]. The main barriers to employment opportunities for those with autism [44] and intellectual disabilities [26,45] included lack of parental support, time, awareness and knowledge of abilities, parental fatigue and unwillingness to facilitate job search.…”
Section: Support and Relationshipsmentioning
confidence: 99%
“…Parents of young adults with developmental disabilities were concerned about the lack of macro-level policies supporting employment [26]. A study done in Namibia [43] revealed that inclusion policies for young adults with visual impairments were not effective in the workplace and were not implemented. Another study completed in both the United States and Norway highlighted that although some policies such as the Americans with Disability Act (ADA) recognized the rights of people with disability in the workplace and promoted "reasonable accommodations," they were unclear about the extent and the range of assistance that should be provided.…”
Section: Services Systems and Policiesmentioning
confidence: 99%
“…Por otra parte, es importante retomar las barreras reportadas por las personas con baja visión relacionadas con el temor a los estereotipos o los estigmas asociados a la discapacidad, pues de alguna u otra manera ponen en evidencia que aún subsiste la postura de la discapacidad como sinónimo de invalidez, imposibilidad, entre otros, lo cual juega un papel fundamental en el refuerzo de la minusvaloración y por lo tanto, en el mantenimiento de la discriminación. Los desafíos que enfrentan las personas con discapacidad visual son multifacéticos y complejos, los cuales a su vez reflejan normas socioculturales profundamente arraigadas que son difíciles de eliminar, como el estigma que conlleva la discapacidad 32 . En algunos estudios se relaciona con algunas personas mostraron una renuencia a etiquetarse como "ciegos" o "personas con discapacidad visual"; las personas con baja visión ven la ceguera como la ausencia total de la vista y, por eso, no sienten que deban aceptar la identidad de ser ciegos debido a su visión restante 33 .…”
Section: Discussionunclassified
“…Besides that, in terms of education, one of the reasons why disabled people are being socially excluded is because of the lack of education they receive from the beginning. This is caused by the limited opportunities for disabled children to participate in the mainstream education (11) due to lack of support in the academic and extracurricular activities (10), denial of education from families or even the society (12), underfunded institutions and unskilled teachers (11).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, in terms of unemployment, as it is related to social exclusion, only 30.5% of the disabled population are employed and 20.8% of the disabled people are found to be unemployed due to several factors including issues on the workplace and employers, lack of psychological support, and personal factors such as severity of their disabilities and also their education level (10). One of the reasons of the low employment rate among disabled people is due to low job satisfaction compared to other nondisabled employees (13) and lack of education which narrow down their options for employment (12). Another impeding factor to employment for them is the losing of their income support if they are able to have a job (10).…”
Section: Literature Reviewmentioning
confidence: 99%